Atividades anticâncer e antiestrogênica de extratos e frações das folhas da "Psidium guajava" L. - Turri, Larissa Shiozawa, 1988- (2018)
Orientadores: João Ernesto de Carvalho, Ana Lúcia Tasca Gois Ruiz, Mary Ann Foglio